2014
DOI: 10.18632/oncotarget.2808
|View full text |Cite
|
Sign up to set email alerts
|

By downregulating Ku80, hsa-miR-526b suppresses non-small cell lung cancer

Abstract: Ku80 is involved in DNA double-strand breaks (DSBs) repair. Ku80 is overexpressed in lung cancer tissues, yet, molecular mechanisms have not been examined. We identified that miRNA, hsa-miR-526b, is bound to the 3′-UTR of Ku80 mRNA, thus decreasing Ku80 expression in NSCLC cells. Hsa-miR-526b was downregulated in NSCLC tissues compared with corresponding non-tumorous tissues, and its expression was inversely correlated with Ku80 upregulation. Overexpression of Ku80 and downregulation of hsa-miR-526b were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…1 Lung cancer is traditionally classified as small cell lung cancer (SCLC) and non-small lung cancer (NSCLC). [2][3][4] NSCLC accounts for 85% of lung cancer cases. 5 NSCLC patient prognosis is poor as nearly half present with metastatic disease at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…1 Lung cancer is traditionally classified as small cell lung cancer (SCLC) and non-small lung cancer (NSCLC). [2][3][4] NSCLC accounts for 85% of lung cancer cases. 5 NSCLC patient prognosis is poor as nearly half present with metastatic disease at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of miR-124 in rats has been proved that can protect against neuronal death and apoptosis by targeting Ku70 [67]. Furthermore, it has recently been shown that Ku80 is overexpressed in lung cancer and overexpressed hsa-miR-526b can downregulate the expression of Ku80, thus causing G0/G1 phase arrest and significantly suppressing the NSCLC growth in vitro and in vivo [68]. After the binding of the Ku70/Ku80 complex to the DSB, the catalytic subunit DNA-PKcs is recruited and activated.…”
Section: Mirnas Mediate Ddr Regulationmentioning
confidence: 99%
“…Further studies have shown that XRCC5 functions in the cellular process, primarily by maintaining telomeres, gene transcription, and the regulation of apoptosis and G2/M phase arrest. 21 Therefore, targeting XRCC5 might be a potential method to inhibit tumor growth. [17][18][19][20] Silencing the expression of XRCC5 could thus significantly inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Silencing the expression of XRCC5 could thus significantly inhibit tumor growth. 21 Therefore, targeting XRCC5 might be a potential method to inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%